RELATIONSHIP OF SCHOOL LEADERSHIP TOWARDS SCHOOL BASED MANAGEMENT (MBS) IN THE FIRST MIDDLE SCHOOL (SMP) NEGERI SE KECAMATAN PAHANDUT CITY OF PALANGKA RAYA - Sogi Hermanto (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
The purposes of this research are to know: (1) the leadership description of State Junior High School Principals in Kecamatan Pahandut Palangka Raya City; (2) the description of School-Based Management of State Junior High School Principals in Kecamatan Pahandut Palangka Raya City; and (3) there is a significant relationship between Principal leadership and school-based management of State Junior High School Principals in Kecamatan Pahandut Palangka Raya City. The method used in this research is quantitative method with correlational research type. The population is 178 teachers of State Junior High School Principals in Kecamatan Pahandut Palangka Raya City where 25% (44 teachers) from it is used for sample. The research results shows that: (1) on the the leadership description of State Junior High School Principals in Kecamatan Pahandut Palangka Raya City, 20,90% in category “very good”, 25,00% in category “good”, 47,73% in category “fair”, and 6,37% in category “poor”; (2) on the description of School-Based Management of State Junior High School Principals in Kecamatan Pahandut Palangka Raya City, 9,09% in category “very good”, 31,82% in category “good”, 50,00% in category “fair”, and 9,09% in category “poor”; (3) after the data had been analyzed, correlation index (rxy) is obtained which is 0,999 > on the significance level 5% = 0,304 and significance level 1% = 0,393. This means that there is a significant positive relationship between Principal leadership and school-based management of State Junior High School Principals in Kecamatan Pahandut Palangka Raya City, in the range 0,900 – 1,00 which means there is a strong or high correlation. The results supports the hypothesis that there is a significant positive relationship between Principal leadership and school-based management of State Junior High School Principals in Kecamatan Pahandut Palangka Raya City.